2014
DOI: 10.2147/ijn.s57353
|View full text |Cite
|
Sign up to set email alerts
|

Bone plate composed of a ternary nano-hydroxyapatite/polyamide 66/glass fiber composite: biomechanical properties and biocompatibility

Abstract: An ideal bone plate for internal fixation of bone fractures should have good biomechanical properties and biocompatibility. In this study, we prepared a new nondegradable bone plate composed of a ternary nano-hydroxyapatite/polyamide 66/glass fiber (n-HA/PA66/GF) composite. A breakage area on the n-HA/PA66/GF plate surface was characterized by scanning electron microscopy. Its mechanical properties were investigated using bone-plate constructs and biocompatibility was evaluated in vitro using bone marrow-deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…To improve the mechanical properties of nHA/PA66 composite, carbon fiber and glass fiber have been added to nHA/PA66 as additives to enhance the mechanical strength of the composite materials. 17,19,20 In this study, graphene was used as an additive to enhance the mechanical properties of nHA/PA66 composite. The large specific surface area of graphene increased the interaction of the polymer materials, which enhanced the mechanical strength of the composite and increased the bioactivity of the material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the mechanical properties of nHA/PA66 composite, carbon fiber and glass fiber have been added to nHA/PA66 as additives to enhance the mechanical strength of the composite materials. 17,19,20 In this study, graphene was used as an additive to enhance the mechanical properties of nHA/PA66 composite. The large specific surface area of graphene increased the interaction of the polymer materials, which enhanced the mechanical strength of the composite and increased the bioactivity of the material.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome this difficulty, many recent studies have used toughening materials, such as glass fibers and carbon fibers, to enhance the mechanical properties of nHA/PA66 composites. 17,19,20 Graphene is another typical additive used for toughening of polymer materials. 21 Graphene has a two-dimensional honeycomb crystal structure of tightly packed SP2 hybridized carbon atoms 22 and is known to be the thinnest, lightest, and strongest material.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has carried out considerable basic research and clinical studies in this field. [4][5][6][7][8] We found that the amount of HA particles deposited on the surface of HA/P66 was relatively low, which affected the rate and quality of the initial osseointegration in HA/P66 implants. Different methods were employed to modify HA/P66 implants to promote osseointegration.…”
Section: Introductionmentioning
confidence: 99%
“…The CF bonded tightly with the HA/PA46, and no cracks were observed between the CF and the HA/PA46 matrix. The results indicated that CF had good compatibility with the HA/PA46 matrix, which was considered to be evidence of a reinforced material with improved mechanical properties compared to that of the matrix [5]. It is obvious that the addition of CF significantly improved the mechanical properties of the HA/PA46 composite.…”
Section: Discussionmentioning
confidence: 92%